Catalpol inhibits TGF‐β1‐induced epithelial‐mesenchymal transition in human non–small‐cell lung cancer cells through the inactivation of Smad2/3 and NF‐κB signaling pathways. Issue 2 (11th September 2018) - Wang, Zuopei; Lu, Yi; Sheng, Bo; Ding, Yi; Cheng, Xiaoke
Abstract: Catalpol, one of the main active ingredients isolated from Rehmannia glutinosa, was reported to possess anticancer activity. However, the role of catalpol in transforming growth factor β1 (TGF‐β1)‐induced epithelial‐mesenchymal transition (EMT) in human non–small‐cell lung cancer (NSCLC) cells has not been elucidated. The objective of this study was to investigate the effect of catalpol on EMT in human NSCLC cells. Our results showed that catalpol significantly inhibited the TGF‐β1‐induced cell migration and invasion of A549 cells, as well as repressed matrix metalloproteinase (MMP)2 and MMP9 expression induced by TGF‐β1 in A549 cells. In addition, catalpol markedly repressed the EMT process in A549 cells in response to TGF‐β1. Furthermore, catalpol prevented the activation of Smad2/3 and nuclear factor κB (NF‐κB) signaling pathways induced by TGF‐β1 in A549 cells. In conclusion, these findings indicated that catalpol inhibits TGF‐β1‐induced EMT in human NSCLC cells through the inactivation of Smad2/3 and NF‐κB signaling pathways. Thus, catalpol may be a promising agent for the treatment of NSCLC. Abstract : Catalpol inhibits transforming growth factor β1 (TGF‐β1)‐induced epithelial‐mesenchymal transition (EMT) in human non–small‐cell lung cancer (NSCLC) cells through the inactivation of Smad2/3 and nuclear factor κB (NF‐κB) signaling pathways. Thus, catalpol may be a promising agent for the treatment of NSCLC.